Modelagem procedural de grupos em ambientes internos - Flach, Laura Mattos (2013)
This work presents the utilization of procedural modelling to populate environments with virtual agents. It uses previously procedurally generated environments together with a crowd simulator to generate the agents locomotion. This work creates groups based on semantic informations of the environment to be populated and on data retrieved from IBGE for the population of Porto Alegre. It also generates behaviour for each member of the group created. These behaviours are coherent to the environment, to the group’s and member’s characteristics and also to time. All of these characteristics and specifications are transformed into seeds, wich makes the persistence of the data possible (the possibility of the regeneration of the context at any moment without the use of data structures) and the execution more simple (the model is fully automatic).